Representasi Pesantren dalam Empat Film Religi Indonesia - Akhya Muhammad Khaidzir (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
This study explores the portrayal of Islamic boarding schools (pesantren), religious scholars (kiai), and Islamic students (santri) in Indonesian religious films, including 3 Doa 3 Cinta (2008), Perempuan Berkalung Sorban (2009), Negeri Lima Menara (2012), and Sang Kiai (2013). Through a qualitative-descriptive approach, the findings reveal that pesantren are often depicted as conservative educational institutions with challenging environments. However, the figure of the kiai is generally portrayed as a wise and open-minded leader who addresses socio-cultural issues and serves as a patriotic figure in Indonesia’s struggle for independence. The santri are commonly shown as resilient and united. Notably, Negeri Lima Menara presents a contrasting depiction by portraying Islamic boarding schools as modern educational institutions that play a significant role in shaping the nation's future generation.